The Impact of Personalized Medicine on Enhancing Quality of Life in Chronic Diseases Management - Hameed, Ekhlas Khalid; Al-Ameri, Laith Thamer; Dulaimi, Ziad; Wahdan, May Yousif; Almomen, Rand (AL-Kindy College Medical Journal, 2025)
Personalized Medicine represents a recent revolution in healthcare practice, focusing on tailoring different therapies to be precise for a specific individual; this is aided by exploring the number of genetic predispositions and lifestyle choices that fit each individual. In this article, the authors utilize and gather recent literature and opinions to discuss the impact of personalized medicine on chronic disease management and patient quality of life. Additional attention is paid to limits and possible ethical issues. Chronic diseases such as Hypertension, Diabetes, and chronic kidney diseases adversely affect multiple health indicators, including Quality of Life (QoL) and well-being. This will have additional impacts on physical and mental health that require further mitigations and to deal with more ongoing mental health. Personalized medicine is a revolutionary step that could be used to manage chronic disease by improving patients’ QoL through tailored treatments. However, it is crucial to handle equity, ethics, and infrastructure issues.